You Can’t Go Home Again: International Students Adjustment to New Cultural Environments - Upadhyay, Prakash (Janapriya Journal of Interdisciplinary Studies, 2018)
Culture shock including its variety of symptoms and outcomes is a completely normal physical and psychological reaction to foreign environments and a part of successful adaptation process–the best and may be even the only means to experience and understand foreign cultures. This article argues that the anxiety and stress related to the adaptation process are shocking but the extent of adjustment does not depend on whether the negative symptoms of culture shock are experienced, but how they are coped with. Adaptation in hosts cultures can be made through different learning processes rather than single learning process that can have positive outcomes in the end, by serving as a hint that something is not right and therefore motivating thinking about how to adjust that can help reduce ethnocentrism and increase acceptance of cultural diversity and appreciation of cultural integrity relating to the challenges of an unfamiliar environment. It is important for spoon- fed theoretically nurtured Nepalese students to grow through this discomfort in order to understand them better and to gain new sensitivities that encourages personal and intercultural competency developments, positive learning experiences leading to increased self-awareness and personal growth in a comparatively developed pragmatic host culture.